Mad men. The final season, part 2 [videorecording (DVD)] - Weiner, Matthew (Lions Gate Entertainment, 2015)
Set in the captivating world of 1960s New York, Mad Men follows iconic ad man Don Draper, his colleagues and his family for one final time.